A globalisation challenge: Preventing a clash between the middle classes of the developed and emerging economies - Andrés Ortega; Miguel Otero-Iglesias; Federico Steinberg (Economics: The Open-Access, Open-Assessment E-Journal, 2018)
Tension is growing between the interests of part of the middle classes that are in decline in the mature economies and the rising ones in emerging markets. The aim of the public policies proposed in this paper is to impede such a clash by avoiding protectionism and de-globalisation, fostering inclusive technological innovation, compensating the losers of globalisation in developed economies and reassuring the winners in emerging economies. Furthermore, it argues that the G20 concept of 'inclusive growth' must overcome the challenges prompted by reduced inequalities between countries, growing inequality within countries and the disruptive impact that accompanies technological innovation.
Keywords: F02; F6; F66; D63; J31; 330; Globalisation; inequality; advanced countries; emerging countries; technology